First description of species of Chvalaea Papp & Földvári from the Neotropical Region (Diptera, Hybotidae, Ocydromiinae) - Ale-Rocha, R. (Zootaxa, 2006)
The species of Chvalaea Papp & Földvári from the Neotropical Region are described for the first time: C. amazonica, sp. n.; C. boliviana, sp. n.; C. catarinensis sp. n.; C. masneri, sp. n. and C. pulchra, sp. n. The male of this genus is described for the first time. A key to the Neotropical species of Chvalaea is also provided.